MEDIA PEMBELAJARAN DIGITAL BAGI GURU SD DI KABUPATEN SUMBAWA - Nurhairunnisah, Nurhairunnisah; Noviati, Wiwi; Merdekawati, Ana; Lestari, Indah Dwi; Sulindra, I Gusti Made (FKIP Universitas Samawa, 2024)
This Community Service is designed with the main target of increasing the ability of elementary school teachers in Sumbawa sub-district in creating digital learning media using Canva. The training material includes an introduction to digital-based learning media as well as practice in creating digital-based learning media. The methods applied include delivering material orally and direct practice using each teacher's laptop. The number of participants was 50 people, including elementary school teachers from Sumbawa sub-district. The results of the program show an increase in teacher abilities, as can be seen from the teacher's enthusiasm in participating in the training. However, teachers still need quite a long time to master the features contained in the Canva platform due to reduced habits in using this technology. Even though the program ran smoothly, the service team experienced problems in integrating the knowledge transfer process from teachers to students due to the limited time the teachers had.